2013
DOI: 10.1016/j.envexpbot.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock control of scion response to water stress in grapevine

Abstract: a b s t r a c tRootstocks play a major role in grapevine tolerance to water stress by controlling and adjusting the water supply to shoot transpiration demand. This study aimed to characterize the influence of rootstock genotypes in the adaptive response of scions to water limiting conditions. The effect of rootstock genotype (140Ru and SO4) was observed in the different availability of water provided to the scions (Cabernet Sauvignon, Grenache, Merlot, Syrah), while scions influenced stomatal control of water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
2
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 43 publications
5
61
2
4
Order By: Relevance
“…Tolerance to cold, drought, salinity, calcareous soils, low pH soils, and aluminum toxicity are some of the tolerance traits that have been demonstrated in rootstocks (Bavaresco et al 1995;Cançado et al 2009;Himelrick 1991;Padgett-Johnson et al 2003). The studies about rootstocks effect on plant adaptation to water stress conditions have recently increased due to the rootstock capacity to extract water from the soil and to control and adjust the water supply to shoot transpiration demand (Alsina et al 2011;Marguerit et al 2012;Tramontini et al 2013). However, studies about variability of WUE in rootstocks are scarce.…”
Section: Rootstock Influence In Wue and Rootstock-scion Interactionsmentioning
confidence: 99%
“…Tolerance to cold, drought, salinity, calcareous soils, low pH soils, and aluminum toxicity are some of the tolerance traits that have been demonstrated in rootstocks (Bavaresco et al 1995;Cançado et al 2009;Himelrick 1991;Padgett-Johnson et al 2003). The studies about rootstocks effect on plant adaptation to water stress conditions have recently increased due to the rootstock capacity to extract water from the soil and to control and adjust the water supply to shoot transpiration demand (Alsina et al 2011;Marguerit et al 2012;Tramontini et al 2013). However, studies about variability of WUE in rootstocks are scarce.…”
Section: Rootstock Influence In Wue and Rootstock-scion Interactionsmentioning
confidence: 99%
“…We reported previously that grapevine rootstocks control g s when water potential decreases (Tramontini et al, 2013) and that root-originated abscisic acid (ABA) limits g s during water stress and upon rehydration after drought events (Lovisolo et al, 2008;Tramontini et al, 2014).…”
Section: Conserved and Novel Grapevine Mirnas Respond To Ds In The Twmentioning
confidence: 99%
“…In parallel, rootstocks affect scion growth vigor and resistance to abiotic stresses (Berdeja et al, 2015;Lovisolo et al, 2016;Lavoie-Lamoureux et al, 2017). Specific rootstocks induce tolerance to DS (Carbonneau, 1985;Soar et al, 2006;Koundouras et al, 2008;Tramontini et al, 2013), and it was shown that particular genetic regions in their genome are linked to the induction of stress tolerance (Marguerit et al, 2012). Thus, rootstock management is considered a promising tool to enhance the resilience of grapevine to water scarcity (Berdeja et al, 2015).…”
mentioning
confidence: 99%
“…In spite of the recognised value of rootstock selection for improving scion's adaptability to specific soil conditions, much of the information available on the drought tolerance of commercially available rootstocks and on differences generated by rootstock/scion combinations has been for long time mainly based on anecdotal evidence or visual comparisons (Soar et al 2006a). In the recent years, more attention has been devoted to the study of the influence of rootstock genotype to scion gas exchange as a consequence of its intrinsic characteristics (genetic, anatomical and physiological specificities of the root system) and of the metabolic control imposed via hormonal signalling (Soar et al 2006a, b;Koundouras et al 2008;Tandonnet et al 2010;Comas et al 2010;Alsina et al 2011;Marguerit et al 2012;Tramontini et al 2013b;Berdeja et al 2015;Ollat et al 2015).…”
Section: General Overviewmentioning
confidence: 99%
“…A recent study evaluated the effect of grafting different cultivars on either a drought-resistant (140Ru) or a drought-sensitive (SO4) rootstock genotype on stomatal regulation (Tramontini et al 2013b). The results suggest that rootstocks can modify the scion's stomatal sensitivity to water stress by shifting the level of stomatal closure towards lower (140Ru) or upper (SO4) Ψleaf independently of the scion's near-iso-or near-anisohydric behaviour.…”
Section: Rootstock-scion Interactionmentioning
confidence: 99%